Modeling Business-Processes of Digital Company - I. V. Manakhova; E. V. Levchenko; A. R. Esina (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The article studies digital companies, models business-processes and formulates growth spots of competitive advantages in conditions of digitalization. Specific features of digital companies are connected with the nature of economic functioning and organization of business-processes, where attaining goals of profitability growth and competitiveness support will rely not only on possession of advanced information technologies but also on competencies in the field of modeling business processes and managing them. The author tries to model businessprocesses of the digital company in three key lines: defining characteristics of the digital company, developing business-processes in Deming PDCA cycle of the digital company, formulating the direction of growth in competitive advantages of the digital company on the basis of business-processes development. Scientific novelty of the research is revealed in the following positions: firstly, key characteristics of the digital company were formulated, secondly, the lines in transforming business-processes in Deming PDCA cycles were systemized, and thirdly, ways of developing business-processes to increase company competitiveness at the stage of digitalization were identified.